Readmissions, costs, and duration to subsequent outpatient visit after hospital discharge among Medicaid beneficiaries utilizing oral versus long-acting injectable antipsychotics in bipolar disorder or schizophrenia. (2nd September 2022) - Tidmore, Laura M.; Keast, Shellie L.; Waters, Heidi C.; Pareja, Kristin L.; Cothran, Terry; Skrepnek, Grant H.
Abstract: Background: Long-acting injectable antipsychotics (LAIs) may reduce hospitalizations versus oral formulations (OAP) in bipolar disorder (BP) and schizophrenia/schizoaffective disorder (SCZ), but the impact on time to outpatient follow-up is less understood. Objectives: To assess hospital readmissions and medical costs among Medicaid beneficiaries with BP or SCZ utilizing OAP or LAI SGAs. Methods: Cross-sectional and longitudinal analyses utilized comprehensive administrative claims of Oklahoma Medicaid beneficiaries (≥18 years) with BP or SCZ between 1 January 2013 and 31 December 2017. Readmissions, total direct medical costs, and psychiatry-related outpatient visits were assessed via generalized linear models and generalized estimating equations, controlling for demographic and clinical covariates. Results: Among 2523 included members, LAI utilization was associated with 1.50 and 1.73 times higher odds of any hospitalization and any readmission, respectively ( p  < .05). Cases involving both BP and SCZ were associated with a 2.40 times higher odds of any readmission, 2.26 times higher number of readmissions, and 24.5% higher costs ( p  < .001). Of the 468 members with a subsequent psychiatry-related outpatient visit, LAIs were associated with a 23.9% shorter duration to outpatient visit and 16.4% lower costs ( p  < .05). Conclusion: In contrast to prior studies, this real-world investigation noted higher hospitalizations and readmissions among LAIs relative to OAP medications, but among members with a hospitalization or ED visit, LAIs were associated with shorter durations to outpatient visits and lower costs. Those with diagnoses of both BP with SCZ had higher odds of any readmission, number of readmissions, and costs relative to those with bipolar disorder alone and may be a key target for interventions. PLAIN LANGUAGE SUMMARY: This study compared long-acting antipsychotics that were administered by injection (LAIs) to antipsychotic agents taken orally (OAPs) among Medicaid members with bipolar disorder and/or schizophrenia. Readmission to the emergency department (ED) or hospital (within 30 days of a previous visit) and costs were observed to be similar with LAIs relative to OAPs. Among members who went to the hospital, a shorter time to psychiatric follow-up outpatient visit and lower costs were observed among those taking LAIs relative to OAPs.